Nanostructure and physical properties of cellulose nanofiber-carbon nanotube composite films. (1st September 2017) - Yamakawa, Akira; Suzuki, Shiho; Oku, Takeshi; Enomoto, Kenta; Ikeda, Motohide; Rodrigue, Joseph; Tateiwa, Keita; Terada, Yoshinobu; Yano, Hiroyuki; Kitamura, Shinichi
Highlights: We prepared cellulose nanofiber multi-walled carbon nanotube (MWNT) composite films. 4- O -methyl-α-d -glucuronoxylan was used as an MWNT dispersion aid in aqueous solution. The composite film had high electrical conductivity and low thermal expansion. MWNT networks in the cellulose nanofiber matrix improve the physical properties. Abstract: We studied the nanostructure and physical properties of cellulose nanofiber-multi-walled carbon nanotube (CNF-MWNT) composite films prepared via MWNT aqueous dispersion using 4- O -methyl-α-d -glucuronoxylan as a MWNT dispersion aid. The composite film had high electrical conductivity (1.05 S/cm), good mechanical properties (Young's modulus: 10.1 GPa, tensile strength: 173.4 MPa) and a low coefficient of thermal expansion (7 ppm/K). FE-SEM imaging showed that the carbon nanotubes dispersed homogeneously and made reinforcing networks in the matrix of cellulose nanofibers. Improvement in the physical properties of cellulose nanofiber film by adding MWNTs is due to this composite structure.